From leisure motivation to recreation specialization: a study on the psychological mechanism of sustainable participation of ice and snow sports participants - Liang, Yuan; Li, Jinglye; Wang, Zhaohong (Frontiers in Psychology, 2025)
IntroductionThis study explores ice and snow leisure behavior, a key topic in China’s ice and snow industry development. Using 914 Chinese participants in leisure-related ice and snow activities as samples, it aims to identify the mechanisms of such behavior and validate hypotheses in a theoretical model.MethodsStructural equation modeling (SEM) was used to analyze the “Leisure Motivation—Leisure Constraints—Leisure Negotiation—Recreation Specialization” model, verifying nine hypotheses on direct and mediating effects.Results(1) Leisure motivation is the main internal driver for ice and snow sports participation; (2) Leisure negotiation strategies are critical to promoting long-term mass participation by alleviating constraints; (3) Restrictive factors (e.g., accessibility, cost) significantly hinder the ice and snow industry’s sustainable development.Discussion/ConclusionsBased on empirical findings, a multidimensional model deconstructing leisure motivation is proposed to enhance internal (e.g., motivation cultivation) and external (e.g., policy) support. Targeted suggestions are offered to boost leisure flexibility and mitigate constraints, providing references for China’s ice and snow leisure industry.